Cutaneous Leishmaniasis of the Eyelids: A Case Series with Molecular Identification and Literature Review - Mohammadpour, Iraj (Korean J Parasitol, 2016)
Cutaneous leishmaniasis (CL) is a protozoan disease which is endemic in Iran. It is transmitted by the Phlebotomus sand fly. The eyelid is rarely involved possibly because the movement of the lids impedes the sand fly from biting the skin in this region. Here, we report 6 rare cases of eyelid CL. The patients were diagnosed by skin scraping, culture, and PCR from the lesions. Skin scraping examination showed Leishmania spp. amastigotes in the cytoplasm of macrophages. Culture examination was positive for Leishmania spp. PCR was positive for Leishmania major and Leishmania tropica. The lesions were disguised as basal cell carcinoma, chalazion, hordeolum, and impetigo. The patients were treated with intramuscular meglumine antimoniate (20 mg/kg/day) for at least 3 weeks. They showed a dramatic response, and the lesions almost completely disappeared. We emphasized the importance of clinical and diagnostic features of lesions, characterized the phylogenetic relationship of isolated parasites, and reviewed the literature on ocular leishmaniasis.